Determinants of tax avoidance: evidence from basic materials sector companies listed on the Indonesia Stock Exchange - Maurel Salsabilah; Prima Apriwenni (Jurnal Ekonomi Perusahaan, 2025)
This study aims to examine the effect of firm size, profitability, and fixed asset intensity on tax avoidance. The population of this research consists of companies in the basic materials sector listed on the Indonesia Stock Exchange (IDX) during 2022–2024. The sampling technique applied was purposive sampling of 112 companies, from which 13 companies were selected as samples over a three-year research period, resulting in a total of 39 sample data points. Data analysis was conducted using IBM SPSS Statistics 25, which included descriptive statistical analysis, pooling data tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results indicate that firm size has a negative effect on tax avoidance, profitability has a positive effect on tax avoidance, while fixed asset intensity has no effect on tax avoidance.